Análise da complexidade do processo de projeto integrado da obra de arquitetura - Denicol, Daniel Antoniazzi (Universidade do Vale do Rio dos Sinos, 2018)
Facing the demand for sustainable development, the architectural design process has suffered extensive transformations. Based on a hierarchical and sequential decision-making model, the usual working methods developed by the construction industry has proved to be inadequate. Emerges, then, the need for an integrated design that, in principle, gathers the conditions for coping with the complexity of the context in which produces contemporary architecture, as well as that inherent complexity of the design process. Still, judging from the complexity and sophistication of the architectural design process, there’s no way to ensure, in case of creative process, that an efficient process is equivalent to a better project. In this way, this work has the objective, through a questionnaire destined to the architects selected in function to the relevance of the work developed in the sustainable project area, to establish the relation between integrated project and the design process in architecture. Through the analysis of the collected data, it was possible to observe that, according to the architects' perception, the multidisciplinary and collaborative work, the performance evaluation and the process management were the aspects that most influenced the design process.
Keywords: Processo de projeto; Projeto integrado; Arquitetura; Design process; Integrated design; Architecture; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo